Media Heterotopias : Digital Effects and Material Labor in Global Film Production - Chŏng, Hye-jin, 1976- (Book collections on Project MUSE., 2018)
Hye Jean Chung challenges the widespread tendency among audiences and critics to disregard the material conditions of digital film production, showing how this emphasis on seamlessness masks the complex social, political, and economic realities of global filmmaking.